Amylase activity is associated with AMY2B copy numbers in dog: implications for dog domestication, diet and diabetes. (28th June 2014) - Arendt, Maja; Fall, Tove; Lindblad‐Toh, Kerstin; Axelsson, Erik
Summary High amylase activity in dogs is associated with a drastic increase in copy numbers of the gene coding for pancreatic amylase, AMY2B, that likely allowed dogs to thrive on a relatively starch‐rich diet during early dog domestication. Although most dogs thus probably digest starch more efficiently than do wolves, AMY2B copy numbers vary widely within the dog population, and it is not clear how this variation affects the individual ability to handle starch nor how it affects dog health. In humans, copy numbers of the gene coding for salivary amylase, AMY1, correlate with both salivary amylase levels and enzyme activity, and high amylase activity is related to improved glycemic homeostasis and lower frequencies of metabolic syndrome. Here, we investigate the relationship between AMY2B copy numbers and serum amylase activity in dogs and show that amylase activity correlates with AMY2B copy numbers. We then describe how AMY2B copy numbers vary in individuals from 20 dog breeds and find strong breed‐dependent patterns, indicating that the ability to digest starch varies both at the breed and individual level. Finally, to test whether AMY2B copy number is strongly associated with the risk of developing diabetes mellitus, we compare copy numbers in cases and controls as well as in breeds with varying diabetes susceptibility. Although we see no such association here, future studies using larger cohorts are needed before excluding a possible link between AMY2B and diabetes mellitus.